Savings constraints and microenterprise development: Evidence from a field experiment in Kenya - Pascaline Dupas; Jonathan Robinson (University of California, Economics Department, 2009)
This paper presents results from a field experiment designed to test whether savings constraints prevent the self-employed from increasing the size of their businesses. We opened interest-free savings accounts in a local village bank in rural Kenya for a randomly selected sample of poor daily income earners (such as market vendors), and collected a unique dataset constructed from selfreported logbooks that respondents filled on a daily basis. Despite the fact that the savings accounts paid no interest and featured substantial withdrawal fees, take-up and usage was high among women. In addition, we find that the savings accounts had substantial, positive impacts on productive investment levels and expenditures for women, but had no effect for men. These results imply that a substantial fraction of daily income earners face important savings constraints and have a demand for formal saving devices (even for those that offer negative de facto interest rates). We also find some suggestive evidence that female entrepreneurs draw down their working capital in response to health shocks, and that the accounts enabled the treatment group to cope with these shocks without having to liquidate their inventories.
Keywords: O12; G21; L26; 330; Familienunternehmen; Selbstständige; Verschuldungsrestriktion; Sparen; Produktivität; Unternehmenswachstum; Weibliche Arbeitskräfte; Kenia